Characteristics of 18F-FAPI-04 PET/CT in patients with peritoneal metastasis and to predict treatment efficacy, a head-to-head comparison with 18F-FDG PET/CT - Yafei Zhang; Mimi Xu; Yu Wang; Fang Yu; Xinxin Chen; Guangfa Wang; Kui Zhao; Hong Yang; Xinhui Su (Cancer Imaging)
Abstract Background 18F-FAPI-04 PET/CT shows promise in detecting peritoneal metastases (PM), but its superiority over 18F-FDG PET/CT for lesion detection and predicting chemotherapy benefit remains unclear. Purpose To compare 18F-FAPI-04 and 18F-FDG PET/CT imaging features in PM and assess predictive value of 18F-FAPI-04 for chemotherapy efficacy. Methods 39 pathologically confirmed PM patients with digestive malignancies underwent concurrent 18F-FAPI-04 and 18F-FDG PET/CT. Semi-quantitative parameters, including SUVmax, tumor/liver ratio (T/L), tumor/mediastinal blood pool ratio (T/B), were analyzed. The tracer uptake was compared via Wilcoxon tests. The relationships between 18F-FAPI-04 uptake with FAP and α-SMA expression were analyzed using Pearson correlation. Patients were divided into different short-term outcome groups (responders vs. non-responders) according to RECIST criteria (v.1.1) after chemotherapy. Post-chemotherapy outcomes were evaluated using logistic regression. Results Patients (median age 62; 16 females, 23 males) included pancreatic (n = 17), cholangiocarcinoma (n = 8), gastric (n = 6), and colorectal cancers (n = 8). 18F-FAPI-04 demonstrated significantly higher SUVmax, T/L, and T/B than 18F-FDG (P < 0.05). Pancreaticobiliary cancers (pancreatic/cholangiocarcinoma) exhibited higher 18F-FAPI-04 uptake than gastroenteric cancers (gastric/colorectal) (P < 0.05), though no differences existed within subgroups. 18F-FAPI-04 parameters positively correlated with FAP and α-SMA expression. In univariate analysis, 18F-FAPI-04 uptake differed significantly between responders and non-responders. Multivariate analysis identified SUVmax as an independent predictor (OR = 1.354, 95%CI:1.025–1.788, P = 0.033). Optimal 18F-FAPI-04 cut-offs for distinguishing outcomes were SUVmax=11.05 (AUC = 0.783; sensitivity = 70.60%, specificity = 80.40%), T/L = 7.53 (AUC = 0.717; 58.82%, 81.82%), and T/B = 8.76 (AUC = 0.751; 64.71%, 86.37%). Conclusion 18F-FAPI-04 PET/CT outperforms 18F-FDG in PM detection, with semi-quantitative parameters predicting chemotherapy response.